Curating contents for ESP virtual classrooms - Striking balance between learner‟s autonomy and didacticism - N, Hema; Sukumaran , Rajeev (International Journal of Psychosocial Rehabilitation, 2020)
Learning is the process of acquiring information induced by a single event or amassed from recurrent experiences. Learning has become an economic necessity to survive. Swift changes and increased complexity of today’s world poses have different demands to be met from education. The challenges in conventional classrooms have caused to search for alternatives. An increase in the acceptance of online learning has made the primary goal of education to be the transmission of knowledge to the students but has tweaked the process to facilitate students’ autonomous learning. The transition of teaching to learning styles should comprise differentiated teaching strategies, evaluation measures. Recent approaches stress upon open-ended self-directed learning and advocates to be flexible and learner-centric, the students are active participants in the learning process. Teachers are demanded to learn, plan, prepare, share materials, and collaborate with their students virtually. In virtual classrooms, as there is enhanced connectivity between the facilitator - learner, teachers should ensure different parameters are in place to help a learner in accomplishing learning outcomes. Adversities such as the lack of quality, the persistence of monologue delivery patterns, the intense requirement of self-discipline, self- direction This paper sheds light on 8 components which could build up an effective virtual classroom experience to overcome adversities and validate against evaluation and metacognition of the learners through LOTUS model, a self-evolved teaching-learning tool